Development of microcomputer-assisted instructional aid in library and information science a case study - Tasanaporn Gadavanij; De Leon, Emelita M.; Cruz, Ma. Divina P. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1983)
An attempt was made to develop a computer-assisted instruction (CAI) aid in library and information science. Specifically, it includes a report on the background, approaches to and methods of designing and developing a CAI package for COMPAIS version II-A, release no. 1 as well as prepare a software package and related documentation for a CAI module implemented on a TRS-80 Model II for the "Online Operations" submodule of COMPAIS version II-A, release no. 1.
The study was divided into two parts: Part one-Systems analysis, design, and development; Part two-Documentation of the study. The General Description of the COMPAIS II-A Manual was used for the CAI package.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: Information science -- Computer-assisted instruction; Library science -- Computer-assisted instruction